V'S STRUGGLE AGAINST THE FASCIST GOVERNMENT SYSTEM IN JAMES MCTEIGUE'S V FOR VENDETTA MOVIE (2005): AN INDIVIDUAL PSYCHOLOGICAL PERSPECTIVE - Ghufron, Burhanudin (2010)
This research investigates how the struggle against the fascist regime reflected in James Mcteigue's V for Vendetta, especially viewed from an Individual Psychological Approach. Therefore, the study analyzes the movie in terms of its structural elements and based on the individual psychological perspective. This study belongs to qualitative study. In this method, the writer uses two data sources; they are primary and secondary data source. The primary data source and the object of the study is the movie V for Vendetta itself, meanwhile the secondary data source are any books of literature and psychology related to this study. The writer collects the data from both primary and secondary data sources in a sort of document evidence. The study comes to the following conclusions. First, based on the structural analysis of each elements consists of character and characterization, casting, setting, plot, point of view, theme, mise an scene, cinematography, sound and editing that are related to each other and become a unity that builds the story impressively. Second, James Mcteigue wants to utter his idea that man has to struggle for his life to reach his goal of life. Through struggle, V as the major character learns to be more superior then before. In his struggle to reach the goal, he psychologically develops his personality to improve his creative power to solve the problems in the V for Vendetta.